Non-biting midges of the genus Paracladopelma Harnisch (Diptera: Chironomidae) from the Russian Far East - Zorina, Oksana V. (Zootaxa, 2006)
The Far Eastern species of the genus Paracladopelma Harnisch, 1923 are revised. Four new species of Paracladopelma are described: P. augustus, P. globosum, P. pseudocamptolabis, and P. urkanensis. Seven species P. doris (Townes), P. furudoprimum Sasa, P. laminatum (Kieffer), P. nais (Townes), P. nereis (Townes), P. nigritulum (Goetghebuer), and P. undine (Townes) are redescribed on the basis of male morphology. Six species are recorded from Russia for the first time. Paracladopelma simantodeea Sasa et al. 1998 is presented as a junior synonym of Paracladopelma furudoprimum Sasa & Arakawa. A key for males of 12 Far Eastern species of Paracladopelma is given.